(untitled) (World Economics and Finance Bulletin, 2022)
This article covers the issues of improving innovative methods of financing small business and private entrepreneurship. Also, the opportunities for improving innovative methods of financing small business and private entrepreneurship were analyzed. In addition, Share of small business and private entrepreneurship and The volume of key indicators of small business and private entrepreneurship in sectors of the economy were analyzed. In addition, it is scientifically proven that the development of small business increases the share of the middle class in society, and at the same time, it is an important factor in ensuring economic, social and political stability in the country